A Population Pharmacokinetic Model of (R)‐ and (S‐) Oxybutynin and Its Active Metabolites After Oral and Intravesical Administration to Healthy Volunteers. (13th January 2021) - Kretschmar, Melanie; Suleiman, Ahmed Abbas; Krause, Petra; Albrecht, Uwe; Stein, Raimund; Rubenwolf, Peter; Fuhr, Uwe; Taubert, Max
Abstract: Oxybutynin is a racemic anticholinergic drug used for the symptomatic treatment of detrusor overactivity. The formation of active metabolites related to tolerability problems depends on the route of administration. The objective of this evaluation was to develop a pharmacokinetic model for oral/intravesical administration as the basis for simulations with different dosages. Data from a published changeover clinical study with 18 healthy adults receiving a single oral dose of 5 mg immediate‐release oxybutynin and single and multiple intravesical doses of 10 mg oxybutynin solution was evaluated. Enantioselective plasma concentrations of oxybutynin and N‐desethyloxybutynin (NDO) were used to establish a population pharmacokinetic model using nonlinear mixed‐effects modeling with NONMEM 7.4.1. For both enantiomers, the data were described well by a 2‐compartment model for oxybutynin with an additional compartment for NDO. Oxybutynin absorption was modeled by transit compartments for oral and first‐order absorption for intravesical application. Bioavailability of the more active (R)‐enantiomer was 7% for oral and 10%‐22% for intravesical administration. In simulations, intravesical doses of 5 to 15 mg (R)‐oxybutynin administered 2 to 3 times daily decreased peak‐trough fluctuations of NDO to 8% compared with 24% after oral administration. The NDO/oxybutynin ratio was reduced from 17 after oral administration to unity. Chronic intravesical versus oral administration of (R)‐oxybutynin generates distinctly lower and less variable concentrations of (R)‐NDO. Pharmacokinetic simulations suggest that exposure for 12.5 mg (R)‐oxybutynin administered twice daily might not compromise efficacy and tolerability compared with exposure for standard thrice‐daily administrations. This assumption needs to be assessed in clinical studies.